2013
DOI: 10.1016/j.peptides.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A mastoparan-derived peptide has broad-spectrum antiviral activity against enveloped viruses

Abstract: Broad-spectrum antiviral drugs are urgently needed to treat individuals infected with new and re-emerging viruses, or with viruses that have developed resistance to antiviral therapies. Mammalian natural host defense peptides (mNHP) are short, usually cationic, peptides that have direct antimicrobial activity, and which in some instances activate cell-mediated antiviral immune responses. Although mNHP have potent activity in vitro, efficacy trials in vivo of exogenously provided mNHP have been largely disappoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 58 publications
(59 reference statements)
0
38
0
1
Order By: Relevance
“…The mastoparan family is a very promising group of potential new drugs. In addition to antiviral activity [35] our results show that mastoparan and some of its analogues may be potential antibacterial agents to treat infections caused by multi-, extended-and pan-drug resistant A. baumannii which have the ability to overcome all the antibiotics administered. Their good in vitro activity against this microorganism allows very high stability in human serum and moderate toxicity in HeLa cells.…”
Section: Resultsmentioning
confidence: 88%
“…The mastoparan family is a very promising group of potential new drugs. In addition to antiviral activity [35] our results show that mastoparan and some of its analogues may be potential antibacterial agents to treat infections caused by multi-, extended-and pan-drug resistant A. baumannii which have the ability to overcome all the antibiotics administered. Their good in vitro activity against this microorganism allows very high stability in human serum and moderate toxicity in HeLa cells.…”
Section: Resultsmentioning
confidence: 88%
“…In pre-incubation, in vivo assays performed with Indian vesicular stomatitis virus (VSV) and MP7-NH2; the peptide made the virus non-infectious and unable to replicate in vivo. In a transmission electron microscopy (TEM) assay, it was observed that VSV virions treated with mastoparan 7 had a significant envelope disruption, appearing to be separated from the capsid [75].…”
Section: Arthropod-derived Avpsmentioning
confidence: 99%
“…Mastoparan-7, a mastoparan analogue, displayed a wide spectrum of antiviral activity against enveloped viruses of five different families (Rhabdoviridae, Poxviridae, Flaviridae, Paramyxoviridae and Herpesviridae) in in vitro assays ( Table 2). Structural studies have indicated pore formation by the insertion of the mastoporan amphiphilic α helix into the viral lipidic envelope, causing its disruption [74].…”
Section: Insect Venomsmentioning
confidence: 99%